Security Governance, Non-Governmental Actors, and the Limited Statehood Legitimacy in the Southeast Asia Landscape: A Conceptual Analysis - Regus, Maksimus; Epafras, Leonard Chrysostomos; Madung, Otto Gusti (UI Scholars Hub, 2025)
This paper discusses security governance in Southeast Asia by looking at the role of non-state actors and the limits of the state in forming security governance. In addition, our study discusses the increasing trend of security threats in the region. We argue that non-state actors play a crucial role in addressing security concerns by patching the gap caused by the limited capability of Southeast Asian states. Our study utilises a qualitative-narrative approach based on data from previous studies, especially studies in the last decade or so. This paper also aims to link the current security governance study with the broader policy-making process in Southeast Asia.